Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Use the Distributive Property to solve the equation. 3(x-6) + 8 = 5x - 2 The solution of the equation is

Sagot :

The equation is given as;

. 3(x-6) + 8 = 5x - 2

The distributive property states that you apply the distributive law of multiplication and division

In this case distribute the left hand side as;

3x - 18 + 8 = 5x - 2

Collect like terms

-18 + 8+2 =5x -3x

-18 + 10 = 2x

-8 = 2x

-8/2 = x

-4 = x